Ten Answers Every Child Welfare Agency Should Provide - Fallon, Barbara; Kartusch, Mark; Filippelli, Joanne; Trocmé, Nico; Black, Tara; Chan, Parlin; Sawh, Praveen; Joh-Carnella, Nicolette (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2019)
A university-child welfare agency partnership between the Factor-Inwentash Faculty of Social Work at the University of Toronto and Highland Shores Children’s Aid (Highland Shores), a child welfare agency in Ontario, allowed for the identification and examination of ten questions to which every child welfare organization should know the answers. Using data primarily from the Ontario Child Abuse and Neglect Data System (OCANDS), members of the partnership were able to answer these key questions about the children and families served by Highland Shores and the services provided to children and families. The Ontario child welfare sector has experienced challenges in utilizing existing data sources to inform practice and policy. The results of this partnership illustrate how administrative data can be used to answer relevant, field-driven questions. Ultimately, the answers to these questions are valuable to the broader child welfare sector and can help to enhance agency accountability and improve services provided to vulnerable children and their families.